A Placement and Sizing of Distributed Generation Based on Combines Sensitivity Factor and Particle Swarm Optimization: A Case Study in Bali’s Power Transmission Networks - Satrya Utama, Ngakan Putu; Hartati, Rukmi Sari; Ariastina, Wayan Gede; Swamardika, Ida Bagus Alit (International Journal of Engineering and Emerging Technology; Vol 2 No 2 (2017): July - December, 2018)
Although many methods for optimizing DG placement and its size in a network with the target of reducing system power losses and voltage profile have already been commended, they still lack from several weaknesses. As a result much can be done about to happen with new algorithms. The proposed algorithms commonly have stressed their formulations on real power losses only and ignored the reactive power losses. Power systems reactive power injection plays an important role in voltage stability control, thus the reactive power losses need to be incorporated in optimizing DG allocation considering their voltage profile improvement. Whereas Particle Swarm Optimization (PSO) approach was proposed for finding the optimal size of DG. This study work intended to apply both real and reactive power flow, power loss sensitivity factors and PSO method in finding the candidate buses for DG placement and its size on Bali’s 150 kV transmission networks. The experimental results show that the proposed algorithm is indeed capable of obtaining a good quality solution efficiently